In the Garden stage 6 - Hunt, Roderick
The familiar characters$1 (BBiff, Chip, and Kipper$1 (Bembark on a magical adventure in their garden, where short, engaging sentences and lively illustrations draw readers in. It$1 (Bs built around fantasy settings that emerge through the (3z(Bmagic key(3y (Bconcept.s
Fiction, part of the Oxford Reading Tree series$1 (Bdesigned to support developing readers through structured progression and repeatable vocabulary.s